Habits and Lifestyles of Coastal Communities in Disposing of Garbage in Madapolo Village, North Obi District - Samili, Asnita Ode; Hasim, Jainudin; Adjam, Syarifuddin; Sasmita, Anggit (CV. Kurnia Grup, 2025)
This study aims to describe the habits and lifestyles of coastal communities in disposing of garbage in Madapolo Village, North Obi District, as well as the factors that affect it. The problem of waste in coastal areas is increasingly complex due to low public awareness, lack of waste management facilities, and strong hereditary habit of throwing garbage into the sea. This study uses a qualitative approach with a descriptive type of research. Data were collected through observation, in-depth interviews, and documentation, then analyzed using thematic analysis methods. The results showed that 74% of people still have poor behavior in disposing of garbage, 78% have habits of less concern for the environment, and 73% have a lifestyle that does not support cleanliness. The educSelatanation factor is one of the main causes, where 92% of respondents are poorly educated, so understanding of the impact of waste on the environment is still limited. In addition, work as a fisherman and other economic activities also shaped the habit of people throwing garbage directly into the sea because it was considered practical. The lack of role of community leaders, weak regulations, and lack of facilities such as garbage dumps also aggravate the condition. This study concludes that behavior change requires comprehensive intervention through environmental education, provision of facilities, involvement of traditional and religious leaders, and the application of social and legal sanctions. With a strategy based on community participation and local wisdom, it is hoped that positive behavior and a clean, healthy, and sustainable coastal environment will be formed.